Efficacy and Effectiveness of Psychosocial Interventions on Behavioral and Psychological Problems of Abused Children in Iran: A Systematic Review - Seyed Hamzeh Hosseini; Seyed Hamed Hosseini; Yazdan Naderi Rajeh (Mazandaran University of Medical Sciences, 2023)
Background: Due to the increasing rate of abuse, several psychosocial interventions have been proposed for the adverse effects of child abuse. However, the conflicting and inconsistent results in this field should be explored. Accordingly, this study aimed to review the effectiveness of psychosocial interventions on the behavioral and psychological problems of abused children in Iran. Methods: A systematic search was conducted in Iranian and international databases, including SID, Magiran, PubMed, Scopus, Web of Science, and Google Scholar search engine. The related articles were searched using the proper keywords. The study samples included male/female patients less than 12 years old. The search process was conducted until June 2023. Two researchers independently screened the titles and abstracts of the search results and then assessed the full texts, selecting the relevant studies. This review emphasized children-focused interventions. Results: A total of 11 qualified studies (8 quasi-experimental, 2 randomized clinical trials, and 1 single subject) out of 239 gathered articles were included in the present systematic review. Samples included 473 patients (198 boys, 247 girls, and 28 unclassified). According to this review, research has confirmed the effectiveness of psychosocial interventions on behavioral and psychological problems of abused children.  Conclusions: The results of this review propose that psychosocial interventions are practical and can be used for children suffering from abuse. Considering their efficacy, such psychosocial interventions are recommended in clinical and educational contexts. Clinical and research implications are presented in the discussion section.